Integrated Management of Environmentalsafety and Technical Risks of Plants Producing Automobiles and Automobile Components - Milan Majernik; Petra Szaryszova; Martin Bosak; Lenka Stofova; Kani Kabdi (Communications - Scientific letters of the University of Zilina, 2015)
The authors, as a result of their scientific and professional activities, present a concept of a future model for integrated management of risks in plants for production of automobiles and their components for contractors. They introduce the concept of a future standardized model of an integrated management system based on sub-aspects, impacts and risks according to the relevant current and upcoming new ISO standards of quality, environment, safety, including ISO 31000 Risks management and ISO/TS 16949. In this article the emphasis is placed on creation of a complex risks register (technical, environmental, safety), for this area of economic activity, their identification, analysis and evaluation within an integrated management system.